Efektivitas Kurikulum Merdeka dalam Meningkatkan Kualitas Pendidikan - Erma Wati; Selvi Amanda; Vhina Putri Rahayuningsih; Rena Revita (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
The Merdeka Curriculum is a new policy developed by the Ministry of Education, Culture, Research and Technology as an effort to restore learning after the COVID-19 pandemic and improve the 2013 Curriculum. This curriculum emphasizes flexibility, student-centered learning, and strengthening character through the Pancasila learner profile. This study aims to examine the effectiveness of implementing Merdeka Curriculum in improving the quality of education in Indonesia. The method used is a literature study with a qualitative descriptive approach. Data were obtained from 25 scientific articles, and after selection, 10 articles were declared relevant. The study results show that the Merdeka Curriculum has a positive impact on the quality of education, such as increasing creativity, independence, 21st century skills, and teacher professionalism. However, the implementation of this curriculum also faces obstacles, such as limited facilities, uneven teacher training, and disparities between education units. Therefore, continuous training, consistent supervision, and equitable policy support are needed to optimize the implementation of Merdeka Curriculum.